2015
DOI: 10.1089/ten.tea.2015.0352
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific miRs in Chondrocyte Maturation: Differentiation-Dependent and Hypertrophy-Related miR Clusters and the miR-181 Family

Abstract: Human mesenchymal stromal cells (hMSC) differentiating toward the chondrogenic lineage recapitulate successive phases of embryonic chondrocyte maturation developing from progenitor cells to hypertrophic chondrocytes. Osteoarthritic cartilage is characterized by an alteration in chondrocyte metabolism and upregulation of hypertrophic differentiation markers. A number of studies point toward a functional role for microRNAs (miRs) in controlling chondrocyte differentiation and development of osteoarthritis (OA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…A recent miRNA expression profile study showed that 169 miRNAs were modulated during hMSC chondrogenesis . Notably, 93 of these miRNAs were significantly downregulated, with the expression of 62 miRNAs being completely lost in the transition from MSC to pre‐chondrocyte stage.…”
Section: Intracellular Anti‐chondrogenic Regulatorssupporting
confidence: 86%
See 1 more Smart Citation
“…A recent miRNA expression profile study showed that 169 miRNAs were modulated during hMSC chondrogenesis . Notably, 93 of these miRNAs were significantly downregulated, with the expression of 62 miRNAs being completely lost in the transition from MSC to pre‐chondrocyte stage.…”
Section: Intracellular Anti‐chondrogenic Regulatorssupporting
confidence: 86%
“…A recent miRNA expression profile study showed that 169 miRNAs were modulated during hMSC chondrogenesis. 70 Notably, 93 of these miRNAs were significantly downregulated, with the expression of 62 miRNAs being completely lost in the transition from MSC to pre-chondrocyte stage. Similar evidence was provided by other studies, 71 suggesting that several microRNAs might exert anti-chondrogenic functions and that suppression of these regulators may be required for chondrogenesis to take place.…”
Section: Micrornasmentioning
confidence: 99%
“…However, DM may also affect chondrogenic power due to interference with additional receptors like the type II receptor ActRIIA40 and may even affect TGFBR2 like the structurally similar LDN-19318941. Delayed addition of DM from day 14 also strongly reduced collagen type II deposition and appeared to delay chondrogenesis in a way that hypertrophic and osteogenic markers were still significantly lower and no collagen type X protein was yet detected at day 42 by Western blotting42. Conclusively this emphasized that an important pro-chondrogenic stimulus was coming from ALK1,2,3,6 downstream signalling at early and late stages of chondrogenesis and its inhibition did not allow an uncoupling of SOX9-driven cartilage matrix production from RUNX2-driven hypertrophy to reach a phenotype similar to AC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activity of MMP-2 and MMP-9 is enhanced by miR-181 mimic [212]. In addition, elevated miR-181a expression is associated with successful chondrogenesis of human MSPCs [213]. However, there are also studies showing a decreased expression of miR-181 family members, including miR-181a, in OA AC cell monolayer cultures, compared to healthy AC cells from younger donors [191,214].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%